Insects associated with fruit, seed and foliage of Uapaca kirkiana (Muell.arg.) (Euphorbiaceae) in Malawi - Meke, Gerald Simeon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.